Leadership And Construction Industry Development In Developing Countries - Ofori, George; Toor, Shamas ur Rehman (Penerbit Universiti Sains Malaysia, 2012)
Leadership is important in all fields of human endeavour. Features of the construction process and construction projects render leadership even more essential. Construction projects are expensive and technically demanding and the project teams are large and diverse. The process is long and involves a large number of discrete and interrelated tasks. Because constructed products influence long-term socioeconomic development in developing countries, poor performance on projects can have severe implications for the nation and its citizens. Thus, the need for effective leadership in construction is even more acute. It may be argued that "effective leadership" is one of the primary answers to the problems of the construction industry, including (and perhaps, especially) problems in developing countries. To this end, greater attention should be given to leadership development. The following questions are addressed in this study. What is leadership? How important is it in construction? How relevant is leadership to construction in developing countries? How has research on leadership developed over time? What is the current status of research on leadership in construction? How can the situation be improved, especially for the leadership needs of developing countries? What are the relevant issues for construction leadership in developing countries? After addressing these questions, the subject of leadership is related to construction industry development. An agenda for research on construction leadership in developing countries is presented.